Biomechanical assessment of a distally fixed lateral extra-articular augmentation procedure in the treatment of anterolateral rotational laxity of the knee - Devitt,BM; Lord,BR; Williams,A; Amis,AA; Feller,JA (American Journal of Sports Medicine, 2019)
Background:Most lateral extra-articular tenodesis (LET) procedures rely on passing a strip of the iliotibial band (ITB) under the fibular (lateral) collateral ligament and fixing it proximally to the femur. The Ellison procedure is a distally fixed lateral extra-articular augmentation procedure with no proximal fixation of the ITB. It has the potential advantages of maintaining a dynamic element of control of knee rotation and avoiding the possibility of overconstraint.Hypothesis:The modified Ellison procedure would restore native knee kinematics after sectioning of the anterolateral capsule, and closure of the ITB defect would decrease rotational laxity of the knee.Study Design:Controlled laboratory study.Methods:Twelve fresh-frozen cadaveric knees were tested in a 6 degrees of freedom robotic system through 0° to 90° of knee flexion to assess anteroposterior, internal rotation (IR), and external rotation laxities. A simulated pivot shift (SPS) was performed at 0°, 15°, 30°, and 45° of flexion. Kinematic testing was performed in the intact knee and anterolateral capsule–injured knee and after the modified Ellison procedure, with and without closure of the ITB defect. A novel pulley system was used to load the ITB at 30 N for all testing states. Statistical analysis used repeated measures analyses of variance and paired t tests with Bonferroni adjustments.Results:Sectioning of the anterolateral capsule increased anterior drawer and IR during isolated displacement and with the SPS (mean increase, 2° of IR; P < .05). The modified Ellison procedure reduced both isolated and coupled IR as compared with the sectioned state (P < .05). During isolated testing, IR was reduced close to that of the intact state with the modified Ellison procedure, except at 30° of knee flexion, when it was slightly overconstrained. During the SPS, IR with the closed modified Ellison was less than that in the intact state at 15° and 30° of fl